Nonpharmacologic management of the behavioural and psychological symptoms of dementia - Brath, Hana, MD; Wiesenfeld, Lesley, MD MHCM; Stall, Nathan M., MD PhD (Canadian Medical Association journal (CMAJ), 2025)
Brath et al discuss nonpharmacologic management of the behavioral and psychological symptoms of dementia. Behavioral and psychological symptoms of dementia (BPSD) are common and negatively affect patient and caregiver outcomes Nearly all people living with dementia develop BPSD. Symptoms vary over time and by type of dementia, and can include agitation, psychosis, depression, apathy, and anxiety. Recognizing and addressing new behavioral or mood symptoms is crucial, as BPSD is associated with increased hospital admissions, institutionalization, functional decline, and caregiver distress. Nonpharmacologic interventions are effective first-line treatments for mild BPSD. Identifying BPSD triggers can guide nonpharmacologic interventions.